Pendampingan Pekerjaan Rumah Singgah Tempat Pemakaman Umum (TPU) Desa Pulau Gadang Kecamatan XIII Koto Kampar - Putra, Agus Alisa; Febryanto; Anisya, Khairun (Journal of Social and Community Service, 2023)
This community service activity aims to assist in the construction of a transit house at the Public Cemetery (TPU) of Pulau Gadang Village, XIII Koto Kampar District. This program is part of an effort to improve community social facilities through technical assistance for construction and counseling to the village government and local communities. The problems faced include limited TPU infrastructure, low public awareness of the importance of maintaining the cemetery environment, and the absence of a structured management system. The solutions implemented include the construction of a transit house, technical education, preparation of a maintenance plan, and active community involvement in the planning and implementation process. This activity also uses geospatial data as a basis for technical planning. The results of the activity are expected to improve the quality of TPU management and strengthen community participation in village development.